47XXY and 47XXX in Scleroderma and Myositis. Issue 6 (29th March 2022) - Scofield, R. Hal; Lewis, Valerie M.; Cavitt, Joshua; Kurien, Biji T.; Assassi, Shervin; Martin, Javier; Gorlova, Olga; Gregersen, Peter; Lee, Annette; Rider, Lisa G.; O'Hanlon, Terrance; Rothwell, Simon; et al.
Abstract : Objective: We undertook this study to examine the X chromosome complement in participants with systemic sclerosis (SSc) as well as idiopathic inflammatory myopathies. Methods: The participants met classification criteria for the diseases. All participants underwent single‐nucleotide polymorphism typing. We examined X and Y single‐nucleotide polymorphism heterogeneity to determine the number of X chromosomes. For statistical comparisons, we used χ 2 analyses with calculation of 95% confidence intervals. Results: Three of seventy men with SSc had 47, XXY ( P = 0.0001 compared with control men). Among the 435 women with SSc, none had 47, XXX. Among 709 men with polymyositis or dermatomyositis (PM/DM), seven had 47, XXY ( P = 0.0016), whereas among the 1783 women with PM/DM, two had 47, XXX. Of 147 men with inclusion body myositis (IBM), six had 47, XXY, and 1 of the 114 women with IBM had 47, XXX. For each of these myositis disease groups, the excess 47, XXY and/or 47, XXX was significantly higher compared with in controls as well as the known birth rate of Klinefelter syndrome or 47, XXX. Conclusion: Klinefelter syndrome (47, XXY) is associated with SSc and idiopathic inflammatory myopathies, similar to other autoimmune diseases with type 1 interferon pathogenesis, namely, systemic lupus erythematosus and Sjögren syndrome.